Families Are More Popular Than Feminism: Exploring the Greater Judicial Success of Family and Medical Leave Laws - Webber, Kate (Columbia Journal of Gender and Law, 2016)
Two federal employment laws advance women’s position in the workplace, but one has been much more successful than the other when employee plaintiffs seek to enforce their rights in court. First, Title VII of the Civil Rights Act of 1964 (“Title VII”) prohibits sex discrimination in the workforce. Plaintiffs seeking to enforce this statute experience one of the lowest success rates of any civil cause of action. On the other hand, the Family Medical Leave Act of 1993 (“FMLA”) provides employees the right to take leave for the birth of a child, medical or family care, and prohibits discrimination against those who use their leave rights. Employees who bring cases under the FMLA have nearly double the chance of winning in court compared with anti-discrimination statutes such as Title VII. The FMLA is more successful despite the fact that, like Title VII’s sex discrimination prohibitions, the FMLA benefits women in particular, providing a key support to their workplace advancement. This Article examines the potential causes of the different litigation success rates of Title VII and the FMLA. In doing so, the Article sheds light on judicial decision-making in employment law and suggests avenues for advocates seeking to change women’s work life for the better.